COMPOSING BACTERIAL CONSORTIUM AS A BASIS OF PROBIOTIC FEED ADDITIVE FOR CARP FISH SPECIES AND EVALUATION OF ITS PROPHYLACTING - Kantor, K.; Proskurnina, I.; Arashkova, A.; Kolomiets, E.; Koshak, Zh.; Gadlevskaya, N.; Rybkina, E. (Eurasian Journal of Applied Biotechnology, 2022)
Isolation and screening of sporulating bacteria possessing hydrolytic activity and displaying antagonistic properties toward carp fish pathogens was carried out; identification of isolates was performed and their preventive-curative action was investigated. Microbial consortium formed by the selective strains laid the basis for test specimen of probiotic feed additive; the optimal dosage of its supplying into composite feed rations was calculated.